Influence of global environmental Change on plankton - Raven, JA; Beardall, J (Oxford University Press (OUP), 2022)
Abstract Much has been published on the effects of ocean acidification on plankton since the original Royal Society 2005 report. In addition to direct effects on primary production, it is clear that ocean acidification also has profound consequences for biogeochemistry. Furthermore, although ocean acidification can have direct effects of on grazers such as copepods, acidification induces changes in nutritional value of phytoplankton which can be passed on up the food chain. There has also been recognition of the complexity of the interactions between elevated CO2 and other environmental factors and this has seen an upsurge in climate change research involving multifactorial experiments. In particular, the interaction of ocean acidification with global warming resulting from the increasing greenhouse effect has been investigated. There has also been research on acidification and warming effects in inland water plankton. These, combined with novel experimental techniques and long term studies of genetic adaptation, are providing better insights to plankton biology and communities in a future world.